When the rain stopped: floods in Rio Grande do Sul and curricular developments (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This is the report of an art teacher whose school was completely flooded during the May’s 2024 floods in Rio Grande do Sul, Brazil. Starting from the concrete reality of a disaster – and also from the trauma suffered by the school community – the text intertwines curricular choices and the current context, addressing issues such as class hierarchies and environmental justice. The presentation and reflection on such classroom practices highlights the planning of a set of pedagogical activities committed to broadening students’ understanding and critical perspective on their social condition, the context in which they are situated, and the repercussions of human action in relation to social inequalities and environmental damage.
Keywords: curriculum; anthropocene; critical environmental education; environmental justice